Strategi Pelayanan Publik Polres Cilegon Sebagai Satuan Kerja Berpredikat Wilayah Bebas Korupsi dan Wilayah Birokrasi Bersih Melayani - Azzunaika, Revani Gena; Havidani, Ardian (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
Decree of the Minister for Empowerment of State Apparatus and Bureaucratic Reform (KEPMENPAN and RB) Number 10 of 2019 concerning the Establishment of Public Service Provider Units in Ministries and Institutions as Locations for Evaluation of Public Services. Cilegon Police is one of the agencies that have launched the development of an Integrity Zone Towards a Corruption Free Area (WBK) and a Clean and Serving Bureaucratic Area (WBBK), especially in the Public Service sector. This study aims to describe what has been carried out by the Cilegon Police in supporting the success of the Integrity Zone in building a Precise Police. This research was motivated by the Cilegon Police as a pilot Police for the development of an integrity zone towards a Corruption Free Area (WBK) and a Clean Serving Bureaucratic Area (WBBM) from the Banten Police. This study uses qualitative research methods, data sources in the form of primary data and secondary data. Primary data obtained from interviews and observations while secondary data obtained from documentation. This research shows that the Cilegon Police has succeeded in carrying out Bureaucratic Reform in the field of Public Services, this is evidenced by the achievement of the title from Kepmenpan RB as a Corruption-Free Area in 2021. The results of this study are expected to provide insight into the Cilegon Police Service Strategy as a work unit with the predicate of Free Area. Corruption and Clean Serving Bureaucratic Areas so that they can have a positive impact on the community in Cilegon City.